Microbiology - Baker, Simon; Nicklin, J.; Griffiths, Caroline (New York : Garland Science, 2011)
"BIOS Instant Notes in Microbiology, fourth edition, is a concise microbiology textbook for undergraduates. All of the important areas of microbiology are covered in a format that is ideal for learning and rapid revision. Each topic begins with a summary of the essential facts-an ideal revision checklist-followed by a description of the subject that focuses on the core information, with clear simple diagrams that are easy for students to understand and recall in essays and examinations"--Provided by publisher.
Rev. ed. of: Microbiology / S. Baker ... [et al.]. 3rd ed. 2007.
Keywords: Microbiology; Microbiology; Microbiological Processes